Influence of CO 2 and nitrogen limitation on the coccolith volume of Emiliania huxleyi (Haptophyta) - Muller, MN; Beaufort, L; Bernard, O; Pedrotti, ML; Talec, A; Sciandra, A (Biogeosciences, 2012)
Coccolithophores, a key phytoplankton group, areone of the most studied organisms regarding their physiologicalresponse to ocean acidification/carbonation. The biogenicproduction of calcareous coccoliths has made coccolithophoresa promising group for paleoceanographic researchaiming to reconstruct past environmental conditions.Recently, geochemical and morphological analyses of fossilcoccoliths have gained increased interest in regard to changesin seawater carbonate chemistry. The cosmopolitan coccolithophore Emiliania huxleyi (Lohm.) Hay and Mohler wascultured over a range of p CO2 levels in controlled laboratoryexperiments under nutrient replete and nitrogen limited conditions.Measurements of photosynthesis and calcification revealed,as previously published, an increase in particulate organiccarbon production and a moderate decrease in calcificationfrom ambient to elevated pCO2. The enhancementin particulate organic carbon production was accompaniedby an increase in cell diameter. Changes in coccolith volumewere best correlated with the coccosphere/cell diameter andno significant correlation was found between the coccolithvolume and the particulate inorganic carbon production. Theconducted experiments revealed that the coccolith volume of E. huxleyi is variable with aquatic CO2 concentration but itssensitivity is rather small in comparison with its sensitivity tonitrogen limitation. Comparing coccolith morphological andgeometrical parameters like volume, mass and size to physiologicalparameters under controlled laboratory conditions isan important step to understand variations in fossil coccolithgeometry.